GAMBARAN BEBAN KERJA PERAWAT TENAGA KERJA SUKARELA DAN PERAWAT APARATUR SIPIL NEGARA - HOTMA ROYANI SIREGAR (Jurnal Education and Development, 2019)
Introduction: Padangsidimpuan General Hospital is a hospital owned by the Padangsidimpuan City government which employs Voluntary Nurses and government Employee Nurses. The purpose of this study is to determine the workload of Voluntary Nurses and Government Employee Nurses. Methode: Research was conducted using quantitatif and qualitative methods using observation techniques work sampling, and interview guidelines. Partisipant has been observed were 15 Voluntary Nurses and 15 Government Employee nurses by using accidental sampling technique. Samples taken were all activities carried out by Voluntary Nurses and Government Employee Nurses in morning shift, such as direct nursing activities, indirect nursing activities, personal activities, and non-productive activities. Results: The results of observations and interviews described workload of voluntary nurses and government employee nurses. After analysed found workload of Voluntary Nurses 381,4 minutes (74,8%) and Government Employee Nurses 314,8 minutes (69,8%). The results of the study suggest that the management of Padangsidimpuan General Hospital to manage nursing staff optimally to achieve quality nursing services.